MacEwan Residence Life Staff: enhancing student leadership - Lade, Tim (My University, 2014)
MacEwan Residence, on the City Centre campus of MacEwan University, opened in 2005 and houses 882 students in 450 suite-style units on a yearly basis. Offering a safe, secure, and academically focused on-campus living experience, MacEwan Residence is committed to assisting in the transition of all students pursuing a postsecondary experience and to offering convenient, affordable housing in the heart of Edmonton, Alberta, Canada. MacEwan Residence delivers this commitment primarily through the Residence Life Staff team, which is made up of 27 residence assistants (RAs) who live within each floor community and who support all residents. It is a well-known fact in Edmonton that there are many off-campus housing options to choose from including condos, apartments, and living with parents. The on-campus experience has to be more than just a convenient and fun place to live, but also needs to be a developmental experience in which relationships can be built, learning can take place, and the cost of residence is a worthwhile investment—in other words, a student doesn’t just a get a bed to put their head in but is able to thrive as a student and an individual.
Keywords: student leadership; residence life staff; student housing